Manajemen Pelayanan Air Bersih Di Desa Maropokot Kecamatan Aesesa Kabupaten Nagekeo Provinsi Nusa Tenggara Timur - Mbusa, Haris Towa Pua; Ansari, Muh Isa; Fatmawati, Fatmawati (Universitas Muhammadiyah Makassar, 2021)
This study pruposed to determine the management of PDAM water services to meet the needs of the community in Maropokot Village, Aesesa District, Nagekeo Regency, East Nusa Tenggara Province. This study used qualitative descriptive. Data collection techniques were observation, interview, and documentation techinques. Data analysis were data reduction, data presentation, and conclusions, while the validity of the using triangulasi of sources, methods, and time. The results of this study showed that the management of PDAM water services included four indicators, namely: 1) Planning at Nagekeo PDAM had been carried out well, but there were still some budget problems that bad not been able to meet the needs, especially efforts to enlarge the pipeline network. 2) Implementation carried out by the Nagekeo PDAM, trough outreach and routine meetings from thr PDAM that visited each village. 3) Coordination of the organizational structure chart could know the duties and authority of each employee. 4) Settlement had been carried out by the Nagekeo Regency PDAM trough two types of supervision, preventive supervision and repressive supervision.